Positive running, a model for high speed running - Bosch, F. (2012)
The author presents with positive running a model for high speed running. Some key points: - The worlds best sprinters run more positive posture than the "also participating". - Control of anterior-posterior pelvic rotation is crucial for hamstring function. - Anterior and posterior tilt of the pelvis plays a important role in making the Hamstring work in its optimum length. Iliopsoas is crucial in Hamstring load - there is no such thing as an overactive iliospoas. - Ground-reaction-force and the whip from the hip. - The problem for running faster is not just applying more force, but more force in shorter time and in the right direction. - The results of this study emphasize the importance of pre-activity and the activity of the leg extensor muscles during the braking phase of running. Their activity is in many cases well above that recorded during maximal voluntary contractions, suggesting that such contractions cannot be used as an indicator of the full activation potential of human skeletal muscle. Thus, features of central programming and reflex regulation seem to differ between isometric maximal voluntary contractions and stretch - shortening cycle exercises such as running. - "Whip from the hip"-technique helps applying force to the ground earlier in stance and is a pattern that can be applied in many movement patterns.